2010
DOI: 10.1007/s11524-010-9503-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist and Pharmacy Staff Experiences with Non-prescription (NP) Sale of Syringes and Attitudes Toward Providing HIV Prevention Services for Injection Drug Users (IDUs) in Providence, RI

Abstract: Increased access to sterile syringes among injection drug users (IDUs) has been correlated with reduced syringe sharing. Many states, including Rhode Island, have legalized non-prescription (NP) sale of syringes in pharmacies. Previous studies have suggested that training pharmacists to provide HIV-related services to IDUs may be an important opportunity to engage IDUs and provide them with such services. However, it is not clear to what extent pharmacy staff are willing to expand their roles in providing serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 17 publications
0
29
0
1
Order By: Relevance
“…U.K. study evaluating a "cascade" training model of clinician peer-to-peer training regarding naloxone found that the number of subsequent peer trainings conducted had been modest (Mayet et al, 2011). Future studies could test alternative training models or evaluate pharmacistled interventions, such as collaborative pharmacy practice agreement approaches (Zaller, Jeronimo, Bratberg, Case, & Rich, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…U.K. study evaluating a "cascade" training model of clinician peer-to-peer training regarding naloxone found that the number of subsequent peer trainings conducted had been modest (Mayet et al, 2011). Future studies could test alternative training models or evaluate pharmacistled interventions, such as collaborative pharmacy practice agreement approaches (Zaller, Jeronimo, Bratberg, Case, & Rich, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A survey of Rhode Island practitioners found that pharmacists felt it was their role to provide equipment and advice to IDUs to prevent the spread of infections and that providing these services in the community pharmacy setting would not disrupt regular pharmacy services. 34 Similarly, pharmacists in New York noted no increase in crime or discomfort among staff and customers following the introduction of clean needle sales, despite fears to the contrary. 15 Furthermore, pharmacists offering needle disposal services and providing sharps containers to IDUs felt that these services had reduced the number of used needles being disposed in their neighbourhoods.…”
Section: 31mentioning
confidence: 99%
“…75 In 268 contrast to quantitative work, which often focus on specific dimensions (i.e., knowledge, 269 attitudes), the qualitative studies take a more in-depth look at pharmacists' experiences related to 270 particular patient populations, including their knowledge, attitudes, beliefs, and perceptions 271 related to working with patients (or potential patients). Notably, although some scholars have 272 examined the patient perspective through surveys e.g.,42, 70,72,81,95,107 and interviews or focus 273 groups, 32,69,77,113,119 or a combinations of methods, 110,116 focused study of patient attitudes, 274 understandings and experiences are less common within this literature. 275…”
Section: Disparity-related Conditions and Processes: Measurement 258mentioning
confidence: 99%
“…Examples of these services 332 included non-dispensing services for those with mental illness, 35,50,70,79 sale of non-prescription 333 syringes (or methadone) to IDUs, 26,29,33,55,[57][58][59][60][62][63][64]66,69,74,76 services for those with, or at risk for, 334…”
Section: Confronting Inequities 14mentioning
confidence: 99%
See 1 more Smart Citation